Faktor yang Mempengaruhi Minat Siswa dalam Mata Pelajaran Pendidikan Jasmani di SMP PGRI 4 Kota Malang - Catur Mardianto, Paulus; Ilham Habibi, Ahmad; Budiono, Dwi (Universitas Insan Budi Utomo, 2024)
This research is motivated by the lack of maximum learning of physical education. This study aims to determine the interest of students in following the learning of physical education in SMP PGRI 04 Malang, East Java. Factors affecting students ' interest in physical education subjects affect the achievement of goals towards a desired thing. Interest in a person cannot occur suddenly but inevitably through a process. The student has an interest from his / her upbringing and acquires attention, interacting with his / her environment so that the interest can grow and develop. This study is quantitative descriptive research. The method used is the survey method. The subjects of this study were all Grade II students recorded in SMP PGRI 04 Malang, amounting to 22 students. The instrument used is questionnaire. Technical analysis is to pour the frequency into the form of a percentage.